Metritis / Pyometra in Angora rabbit - DAS, G K; RISAM, K S (The Indian Journal of Animal Reproduction, 2023)
Present communication records the occurrence of metritis I pyometra in Angora rabbit from a subtemperate climate ofIndia.
Keywords: Metritis; pyometra; rabbit; Angora